Recent advances in polymeric microparticle-based drug delivery systems for knee osteoarthritis treatment - Wang, Guangxin; Zhang, Xin-an; Kapilevich, Leonid; Hu, Mingjie (Frontiers in Bioengineering and Biotechnology, 2023)
Sustained delivery of therapeutic agents in the treatment of osteoarthritis (OA) has been a challenge due to poor bioavailability and high joint clearance of drugs. Intra-articular (IA) drug delivery strategy is a promising approach to improve the prognosis of OA patients, for which various polymer materials have been used as drug carriers due to their attractive delivery properties, to slow or even reverse the progress of OA by prolonging the duration of therapeutic agent residence in the joint. This article focuses on the recent advances in natural and synthetic polymer-based microsphere drug delivery systems for treating knee osteoarthritis. It evaluates the translational potential of some novel formulations for clinical application.